Industrial CFD and Fluid Modeling in Engineering—2nd Edition - Francesco De Vanna (Fluids)
Following the success of the first edition of “Industrial CFD and Fluid Modeling in Engineering”, this second edition continues to showcase cutting-edge research that pushes the boundaries of computational fluid dynamics (CFD) in addressing complex industrial flow problems [...]